Cuidados de enfermería en paciente con evento cerebro vascular no especificado - Villamar Verduga , Vanessa Alejandra (2025)
Cerebrovascular events are a leading cause of death and disability worldwide. One of the most significant and modifiable risk factors for the development of CVD is hypertension, which is a major contributor to both ischemic and hemorrhagic strokes. The present case study aimed to apply nursing plans in patient with unspecified cerebrovascular event, thus improving their clinical status, using Marjory Gordon's functional patterns tool, together with the application of NANDA, NOC and NIC taxonomies to prioritize nursing interventions. These actions allowed the identification of several nursing diagnoses, such as impaired ventilation, impaired urinary elimination, acute confusion, and tendencies to engage in health risk behaviors. The approach to each diagnosis focused on specific interventions, such as management of constant vital signs, placement of oxygen support, bladder catheter cleaning and diuresis quantification, physical rehabilitation, health education and promotion of patient autonomy in their care to achieve good adherence to treatment. The response to treatment was positive, with significant improvements in vital signs and the patient's understanding of her health condition. The importance of comprehensive, patient-centered care was highlighted. This case study highlights the importance of applying nursing interventions in an accurate and timely manner in the management of a cerebrovascular event, highlighting the need for a multidisciplinary and evidence-based approach to improve outcomes and prevent a cerebrovascular event through education.